2018
DOI: 10.1096/fj.201802075r
|View full text |Cite
|
Sign up to set email alerts
|

Microgravity‐induced hepatogenic differentiation of rBMSCs on board the SJ‐10 satellite

Abstract: Bone marrow‐derived mesenchymal stem cells (BMSCs) are able to differentiate into functional hepatocytelike cells, which are expected to serve as a potential cell source in regenerative medicine, tissue engineering, and clinical treatment of liver injury. Little is known about whether and how space microgravity is able to direct the hepatogenic differentiation of BMSCs in the actual space microenvironment. In this study, we examined the effects of space microgravity on BMSC hepatogenic differentiation on board… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 61 publications
0
13
0
Order By: Relevance
“…Tan et al [29] reported about a reduction in focal adhesions in melanoma cells exposed to s-µ g . In space on board the SJ-10 satellite, the mechanosensitive molecules β 1 -integrin, β-actin, α-tubulin, and others were elevated, whereas among others vinculin was down-regulated in bone marrow-derived mesenchymal stem cells [40]. In addition, the authors observed an accumulation of microtubules and vimentin through the altered expression and location of focal adhesion complexes [40].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tan et al [29] reported about a reduction in focal adhesions in melanoma cells exposed to s-µ g . In space on board the SJ-10 satellite, the mechanosensitive molecules β 1 -integrin, β-actin, α-tubulin, and others were elevated, whereas among others vinculin was down-regulated in bone marrow-derived mesenchymal stem cells [40]. In addition, the authors observed an accumulation of microtubules and vimentin through the altered expression and location of focal adhesion complexes [40].…”
Section: Discussionmentioning
confidence: 99%
“…Western blot analysis, gel electrophoresis, trans-blotting, and densitometry were carried out following routine protocols as described previously [38,39,40]. Following lysis and centrifugation, aliquots of 30 µ g were subjected to SDS-PAGE and Western blotting.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, the number of hMSCs with a disordered actin cytoskeleton gradually increased and the cells showed a contracted phenotype [85,86]. Besides, in rat MSCs on board the SJ-10 Satellite, the expression of VCAM1, ICAM1, CD44, and vinculin was reduced along with depolymerization of actin filaments and the accumulation of microtubules due to true weightlessness in space [87]. With experiments in vitro and in vivo, it was demonstrated that redistribution of vinculin also occurred in hMSCs after 6 h of simulated microgravity [85], and the number of vinculin-containing focal adhesions was decreased in rat MSCs after 28 days of HLU [88].…”
Section: Microgravity Regulates Adhesion and Fate Determination Of Stem Cellsmentioning
confidence: 99%
“…Beyond that, other researchers have demonstrated that although microgravity destroys the adhesion ability of stem cells, it can also drive cell differentiation and transdifferentiation. Lu et al demonstrated that space microgravity not only reduces adhesion molecule expression but also promote the hepatogenic differentiation of MSCs [87]. The upregulation of hepatocyte-specific cytokeratin 18 and albumin makes cell mature [87].…”
Section: Microgravity Regulates Adhesion and Fate Determination Of Stem Cellsmentioning
confidence: 99%
“…In recent studies, we subjected thyroid and breast cancer cells and endothelial cells, which had been cultured for a few days on ground, in Space or on a Random Positioning Machine (RPM) simulating microgravity, to mass spectrometry or microarray gene analyses. These high throughput omics technologies unveiled thousands of proteins or genes [5][6][7][8], including gravity-sensitive cell adhesion proteins such as integrins, which form alpha-beta dimers [9,10], cadherins [6,11,12], and other cell adhesion molecules [13][14][15] as well as CD44 [16], whose sensitivity to microgravity has repeatedly been described [17]. CD44 is a cell surface receptor that plays a role in cell-cell interactions, cell adhesion, and migration, helping the cells to sense and respond to changes in the tissue microenvironment [18,19].…”
Section: Introductionmentioning
confidence: 99%